Improvement of the cardiorespiratory endurance, perception of the effort and walking performance of the old people of the hospice Saint Marc of Kingasani by the practice of the adapted physical activities - Bofosa, Teddy; Kam, Eric; Miangindula, Betty; Njimbu, François; Nkiama, Constant (The European Research Journal, 2019)
Objective: To verify the effects of functional rehabilitation associated with a program of physical activities adapted to the biomechanical parameters and perception of the effort of the elderly.Methods: A longitudinal experimental study of 30 elderly people living in the old people's home was conducted during a 6-month period from July 2017 to January 2018. It consisted in evaluating the biomechanical parameters and perception of the effort of older people a functional rehabilitation program associated with the practice of adapted physical activities.The parametric t test of student was used to compare the averages of different parameters of study before and after the intervention program.The statistical test results used were interpreted at the p